2001
DOI: 10.4049/jimmunol.166.3.1635
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Arthritis Induces Down-Regulation of G Protein-Coupled Receptor Kinases in the Immune System

Abstract: G protein-coupled receptors (GPCR) play a crucial role in the regulation of the immune response by, e.g., chemokines, PGs, and β2-adrenergic agonists. The responsiveness of these GPCRs is turned off by the family of G protein-coupled receptor kinases (GRK1–6). These kinases act by phosphorylating the GPCR in an agonist-dependent manner, resulting in homologous desensitization of the receptor. Although GRKs are widely expressed throughout the body, leukocytes express relatively high levels of GRKs, in particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(77 citation statements)
references
References 47 publications
5
69
0
3
Order By: Relevance
“…Interestingly, the level of expression of GRK2, 3, and 6 in leukocytes is known to be tightly regulated (10). For example, we have shown that in patients with rheumatoid arthritis or in rats after development of adjuvant arthritis or experimental autoimmune encephalomyelitis, the level of GRK2, 3, and 6 is reduced by 50 -80% in leukocytes from the blood or spleen (11)(12)(13). In addition, there is evidence that cytokines as well as oxygen radicals can regulate the level of expression of GRK in leukocytes and other cell types (11,14,15).…”
Section: P Olymorphonuclear Neutrophils (Pmn)mentioning
confidence: 98%
“…Interestingly, the level of expression of GRK2, 3, and 6 in leukocytes is known to be tightly regulated (10). For example, we have shown that in patients with rheumatoid arthritis or in rats after development of adjuvant arthritis or experimental autoimmune encephalomyelitis, the level of GRK2, 3, and 6 is reduced by 50 -80% in leukocytes from the blood or spleen (11)(12)(13). In addition, there is evidence that cytokines as well as oxygen radicals can regulate the level of expression of GRK in leukocytes and other cell types (11,14,15).…”
Section: P Olymorphonuclear Neutrophils (Pmn)mentioning
confidence: 98%
“…Elucidating the mechanisms by which the ␤-arrestin-GRK system participates in chemotactic signaling should enhance understanding of the molecular basis for this extraordinarily important and complex cellular process. It also may shed light on the pathophysiology of certain inf lammatory conditions such as rheumatoid arthritis in which lymphocyte GRK6 is dramatically down regulated (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…These proteins act as GTPase activating proteins for Gα subunits and can also function as effector antagonists of specific Gα subunits, thereby attenuating signaling through GPCRs such as chemokine receptors. In addition, physiologic modulators of G protein signaling, such as RGS and G protein receptor kinases (75,76), represent potential new therapeutic targets in the treatment of atopy and other inflammatory conditions. Thus, the particular spectrum of GPCR proteins and their expression levels within a cell will determine the duration and magnitude of G protein signaling initiated by chemokines for immunomodulating drug targets.…”
Section: Emerging New Drug Targets For Immune-related Herbal Drug Devmentioning
confidence: 99%